Como se apresentam as ocupações de pessoas com doença respiratória crônica? - LIMA, Raiany Duarte de (2023)
Chronic respiratory disease has been affecting a larger number of people each year, the most common being asthma, chronic obstructive pulmonary disease (COPD) and bronchiectasis. These are diseases that cause several damages such as decreased physical capacity, changes in habits, functionality, human movement and, consequently, can generate changes in occupational routine. Occupation can be characterized as activities that are performed in the daily life of each person, such as work, leisure and self-care. Due to the changes resulting from the disease process and its possible changes in daily life, the objective of this research was to understand how the occupations of people with chronic respirat ory disease are presented. It is a qualitative research. It was carried out at a reference Physiotherapy and Occupational Therapy, collected through an open interview, later transcribed and treatment of the information by Bardim content analysis. Twenty-two people participated in the research. The study pointed out that there are changes in the occupational form, meaning and meanings attributed to the activities, which were potentiated or modified with the presence of a chronic respiratory disease. The occupations most affected were work and household chores. The study contributed to the knowledge of the academic and scientific community, regarding the individual, their occupations health and well-being.